Detection and Investigation of Atypical Porcine Pestivirus within a Breed-to-Finish Farm and Off-Site Nursery and Finisher Locations - C. Grace Elijah; Cassandra K. Jones; Jason C. Woodworth; Rachel Palinski; Chad B. Paulk; Tom Petznick; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2021)
Atypical porcine pestivirus (APPV) has been associated with congenital tremors (CT) and splay leg (SL) in piglets of infected dams. The major cost of this virus is the increased pre-weaning mortality due to CT or SL interfering with the piglet’s ability to nurse and move around the farrowing stall. A commercial farrow-to-finish farm with replacement gilts coming from an off-site genetic multiplier farm, and semen delivery from a commercial boar stud began to see an increase of CT and SL in the farrowing room in early 2020. Diagnostics on clinically affected pigs’ samples identified APPV RNA and no other suspected pathogen. At this point, the origin of the virus and means of introduction into the farm was unknown since the farm had no previous clinical cases of CT or SL prior to this investigation. The two hypothesized routes were the introduction of replacement gilts or incoming semen doses. Therefore, the objectives of this investigation were to determine the prevalence of clinical APPV cases at the farrow-to-finish farm, understand the route of introduction of APPV into the farrowto- finish farm, and understand the prevalence of APPV viremia within a population of offspring from a gilt multiplication farm through an off-site nursery and finisher barn. Farrowing records from the farm were analyzed for the presence of CT or SL and parities of females with affected litters. Blood samples were collected at two different times from the new group of replacement gilts and maternal barrows at the isolation nursery barn. Serum and oral fluids were collected from the same pigs at an off-site finisher barn to determine APPV persistence. The APPV sequencing was conducted on a serum sample from a gilt housed at the isolation nursery intended as a replacement gilt for the farrow-to-finish farm, semen dose utilized at the farrow-to-finish farm, and serum of a clinically affected piglet in the farrowing room of the farrow-to-finish farm. Overall, the prevalence of affected litters within batch farrowing groups ranged from 0 to 31%. The prevalence of APPV within samples pooled by pens (5 pigs) ranged from 37.5 to 77.5%, while individual prevalence ranged from 20 to 40%. When followed to the finisher, the same group of pigs had an APPV prevalence in serum ranging from 0 to 26%, while oral fluid prevalence was 100%. Sequencing results indicated that the virus circulating in clinically affected piglets was the most similar to an incoming semen dose. In summary, introduction of APPV into a naïve herd is associated with an increase in clinical CT and SL. While APPV is present in herds previously exposed to APPV, the APPV RNA remains detectable in serum and oral fluids with no clinical disease. To decrease the chance of infection to a naïve herd, quarantines should be implemented for all introductions. Additionally, semen should be screened for APPV presence if there is a recent onset of clinically affected piglets with CT or SL with no other explanation. The APPV RNA was detected in group oral fluids, suggesting the technique may be used to screen incoming animals.
Keywords: Atypical porcine pestivirus; finisher; nursery; over time prevalence